[SOLVED] Diff Eq problem 1. The problem statement, all variables and given/known data y'' - 3y' - 4y= 5e^-x - 3x^2 + 7 2. Relevant equations I think I would need to find complimentary solution, then the particular solution using variation of parameters y=y(c) + y(p) 3. The attempt at a solution y(c)= r^2-3r-4=0 (r-4)(r+1)=0, r=4,-1 y(c)=c(1)e^4x+c(2)e^-x this is where I get stuck as I do not know what to use for y(p), would it be y(p)=Axe^-x + Bx^2 + Dx +E ??? y'(p)=Ae^-x - Axe^-x + 2Bx + D y"(p)=-Ae^-x -Ae^-x +Axe^-x +2B= Axe^-x - 2Ae^-x + 2B (Axe^-x - 2Ae^-x + 2B) - 3(-Axe^-x + Ae^-x + 2Bx + D) -4(Axe^-x +Bx^2 + Dx +E)= (5e^-x - 3x^2 + 7) am I even heading in the right direction?